Belajar Komputer Tanpa Komputer: Solusi Pemerataan Pendidikan di Daerah 3T (Current Research in Education: Conference Series Journal, 2022)
Education is a change in human behavior and absolutely which is a must and is aimed at every human being. With that, education must be obtained by every human being equally. However, the equitable distribution of education in Indonesia has not been fully implemented. Judging from the data from the Ministry of Education and Culture, it shows that 75% of education in Indonesia does not meet the minimum education service standards, especially in rural / 3T areas (remote, disadvantaged, underdeveloped). This is of course very worrying, considering that the world has entered the digital era. Based on the preliminary study, the main cause is the lack of facilities. The solution we can offer is the unplugged method. The unplugged method is a learning method specifically for ICT subjects and does not use computers as teaching aids. To test the effectiveness of this method, this study used a quasy experimental design method. To date, we have reached the first stage of the research procedure. By using this unplugged method, it is possible for teachers to teach teaching and learning ICT without having to use computer media. The unplugged method is still developing to be able to solve the problem of how students can understand computer work without having to use a computer. We think that for rural areas the / 3T unplugged method is the right solution. We really hope that the knowledge of this unplugged method can be a solution to the problem for the lack of ICT teaching and learning facilities in rural areas.